Privatization and the Future of Canadian Healthcare - Babony, Alexander (Global Health: Annual Review, 2019)
The debate over the benefits of public vs private healthcare services in Canada has risen again. While most Canadians agree there should be some form of taxpayer-funded health insurance, disagreements arise over what extent governments should be involved in providing this. In Canada, the prospect of further privatizing healthcare is something few politicians have had the courage to address; it is political suicide. Ontario Premier Doug Ford was recently forced to address leaked documents that (according to the opposition New Democrats) suggested that his administration was intending to implement some degree of private health services in Ontario.1 The public backlash to this was swift and harsh. This article will make the case for opening the healthcare industry to market forces while preserving a separate public system that many in our country currently rely on. It will address the benefits for this rationale from a values-based perspective in an attempt to convince readers on both sides of the political spectrum